The Use of Conventional and New Music Media: Implications for Future Technologies - Brown, Barry A. T.; Geelhoed, Erik; Sellen, Abigail (Hewlett-Packard Labs Technical Report, 2001)
A number of new technologies such as the MP3 music compression format and the Napster file sharing network are creating new opportunities for consumers’ activities with music media. In this paper we explore current practice with both conventional and new forms of media in order to better understand what the future may hold for music consumers. We interviewed 36 music enthusiasts: 12 teenaged and 12 adult conventional music users, and 12 early adopters of MP3 technologies. The results show that rather than new music technologies replacing the old, they supplement current formats by allowing users to exploit a different set of affordances. We discuss these uses drawing implications for new music devices, services and software.